2020 IEEE International Women in Engineering (WIE) Conference on Electrical and Computer Engineering (WIECON-ECE) 2020
DOI: 10.1109/wiecon-ece52138.2020.9397933
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Drawn Emoji Recognition using Convolutional Neural Network

Abstract: Emojis are like small icons or images used to express our sentiments or feelings via text messages. They are extensively used in different social media platforms like Facebook, Twitter, Instagram etc. We considered hand-drawn emojis to classify them into 8 classes in this research paper. Hand-drawn emojis are the emojis drawn in any digital platform or in just a paper with a pen. This paper will enable the users to classify the hand-drawn emojis so that they could use them in any social media without any confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They also suggested that additional improvements in CNN models could be achieved by collecting more data and exploring the use of generative adversarial networks for generating emoticons. Akter et al [30] presented a system for detecting and categorizing hand-drawn emojis into eight distinct classes using a CNN model. A local dataset of 4,000 images was generated and 97% accuracy can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that additional improvements in CNN models could be achieved by collecting more data and exploring the use of generative adversarial networks for generating emoticons. Akter et al [30] presented a system for detecting and categorizing hand-drawn emojis into eight distinct classes using a CNN model. A local dataset of 4,000 images was generated and 97% accuracy can be achieved.…”
Section: Introductionmentioning
confidence: 99%